Enhanced Bacitracin Production by Systematically Engineering S-Adenosylmethionine Supply Modules in Bacillus licheniformis - Cai, Dongbo; Zhang, Bowen; Zhu, Jiang; Xu, Haixia; Liu, Pei; Wang, Zhi; Li, Junhui; Yang, Zhifan; Ma, Xin; Chen, Shouwen (Frontiers in Bioengineering and Biotechnology, 2020)
Bacitracin is a broad-spectrum veterinary antibiotic that widely used in the fields of veterinary drug and feed additive. S-Adenosylmethionine (SAM) is a critical factor involved in many biochemical reactions, especially antibiotic production. However, whether SAM affects bacitracin synthesis is still unknown. Here, we want to analyze the relationship between SAM supply and bacitracin synthesis, and then metabolic engineering of SAM synthetic pathway for bacitracin production in Bacillus licheniformis. Firstly, our results implied that SAM exogenous addition benefited bacitracin production, which yield was increased by 12.13% under the condition of 40 mg/L SAM addition. Then, SAM synthetases and Methionine (Met) synthetases from B. licheniformis, Corynebacterium glutamicum and Saccharomyces cerevisiae were screened and overexpressed to improve SAM accumulation, and the combination of SAM synthetase from S. cerevisiae and Met synthetase from B. licheniformis showed the best performance, and 70.12% increase of intracellular SAM concentration (31.54 mg/L) and 13.08% increase of bacitraicn yield (839.54 U/mL) were achieved in resultant strain DW2-KE. Furthermore, Met transporters MetN and MetP were respectively identified as Met exporter and importer, and bacitracin yield was further increased by 5.94% to 889.42 U/mL via deleting metN and overexpressing metP in DW2-KE, attaining strain DW2-KENP. Finally, SAM nucleosidase gene mtnN and SAM decarboxylase gene speD were deleted to block SAM degradation pathways, and bacitracin yield of resultant strain DW2-KENPND reached 957.53 U/mL, increased by 28.97% compared to DW2. Collectively, this study demonstrated that SAM supply served as the critical role in bacitracin synthesis, and a promising strain B. licheniformis DW2-KENPND was attained for industrial production of bacitracin.